IDENTIFICATION OF LAND SUITABILITY OF (Holothuria scabra) BASED ON CHEMICAL PARAMETERS USING GEOGRAPHIC INFORMATION SYSTEMS IN WEST LOMBOK WATERS - Marsoedi, Marsoedi; Guntur, Guntur; Mulyani, Laily Fitriani (Jurnal Perikanan Unram, 2020)
Sea cucumbers are a group of invertebrate animals of the phylum Echinodermata Holothurioidea class. Sea cucumbers include important components in the food chain because of its role as the sediment feeder and suspended feeder. It is therefore necessary that adequate information that can be used for sea cucumber management in a sustainable manner. One method used is to use geographic information system (GIS). This method can be used to make it easier to know the location of its spreading, so the development of sea cucumber (Holothuria scabra) in aquaculture can be achieved optimally. The purpose of this study was to analyze the suitability of the sea cucumber cultivation areas using GIS applications were presented in map form suitability sea cucumber cultivation area (H. scabra) in West Lombok Waters. This study was conducted on 17th October - 27th November 2016 at Gili Asahan, Gili Layar, and Gili Gede in West Sekotong, Lombok, West Nusa Tenggara. Data was collected by survey methods, such as primary and secondary data directly related to the life of sea cucumbers. Based on chemical parameter the result of this research in West Lombok were pH 6,82 – 7,50, salinity 32 – 34 ppt and DO 6,19 – 6,52 mg/L. The location of land suitability for very appropriate category contained in Gili Gede, Gili Asahan appropriate category and the category is not appropriate in Gili Layar.